Considering change with archaeological data: reevaluating local variation in the role of the ~4.2k BP event in Northwest China - Jaffe, Y; Hein, A (SAGE Publications, 2020)
Over the past two decades, environmental studies in research on prehistoric China have been gaining popularity and importance. For Northwest China in particular, climate change, especially the so-called ~4.2k BP event has been seen as the main reason for an alleged collapse of Late Neolithic societies and a transition to pastoral-heavy economies and mobile lifeways. Yet, these explanatory models tend to rely on limited archaeological and environmental data and non-contemporaneous historical data, resulting in simplistic causal relationships between environmental changes and social response.